Analytical modelling of local contact behaviour in incremental sheet forming - Hui Zhu; Hengan Ou (Journal of Materials Research and Technology)
The localised deformation is central to incremental sheet forming (ISF). A detailed understanding of the interfacial contact behaviour between the forming tool and the blank sheet in ISF is significant to a number of important areas of current ISF research including ISF thermomechanical behaviour, deformation and failure, ISF workpiece surface finish and ISF tooling. This study develops analytical models for the contact behaviour including the contact area, the maximum contact pressure and the pressure distribution by considering the localised tool-sheet contact condition and the contact mechanics of elastic-plastic materials. The nonuniform distribution of contact pressure in both circumferential and meridional directions are investigated and modelled. The analytical models are implemented and validated by ISF of Titanium Grade 1 (TA1) and heat-assisted friction stir ISF (HAFS-ISF) of polyether ether ketone (PEEK). A good agreement is obtained between the analytical prediction and finite element (FE) simulation, the validity of which is confirmed by comparing with the experimental results. The developed analytical models can give comparable but faster prediction of the localised contact pressure although there is still a scope for improvement.